Immobilization of malate dehydrogenase on carbon nanotubes for development of malate biosensor - Ruhal, A.; Rana, J. S.; Kumar, S.; Kumar, A. (Cellular and Molecular Biology, 2012)
An amperometric malic acid biosensor was developed by immobilizing malate dehydrogenase on multi-walled carbon nanotubes (MWCNT) coated on screen printed carbon electrode. The screen printed carbon electrode is made up of three electrodes viz., carbon as working, platinum as counter and silver as reference electrode. Detection of L-malic acid concentration provides important information about the ripening and shelf life of the fruits. The NADP specific malate dehydrogenase was immobilized on carboxylated multiwalled carbon nanotubes using cross linker EDC [1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide] on screen printed carbon electrode. An amperometric current was measured by differential pulse voltammetry (DPV) which increases with increasing concentrations of malic acid at fixed concentration of NADP. Enzyme electrode was characterized by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The detection limit of malic acid by the sensor was 60 - 120 µM and sensitivity of the sensor was 60 µM with a response time of 60s. The usual detection methods of malic acid are nonspecific, time consuming and less sensitive. However, an amperometric malic acid nanosensor is quick, specific and more sensitive for detection of malic acid in test samples.